Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Di SiCangkir Coffee - Fahri, Muhammad Dwi; Frida Aprilia; Sonny Fransisco Siboro (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
The purpose of this study was to determine (1) the effect of product quality on consumer satisfaction in a cup of Coffee (2) the effect of service quality on consumer satisfaction in a cup of Coffee (3) the effect of product quality and service quality on consumer satisfaction in a cup of Coffee. This study was conducted on a cup of Coffee using quantitative descriptive method. The sample in this study amounted to 100 respondents coffee cup consumers. Data collection technique is by filling out a questionnaire through google form with some questions, then processed using SPSS 26. The results of the T-test showed that there is no partial influence between product quality and consumer satisfaction and there is a partial influence between the quality of service to consumer satisfaction. Simultaneous influence between product quality and service quality on consumer satisfaction. which means that product quality and service quality have a simultaneous influence on consumer satisfactionThe purpose of this study was to determine (1) the effect of product quality on consumer satisfaction in a cup of Coffee (2) the effect of service quality on consumer satisfaction in a cup of Coffee (3) the effect of product quality and service quality on consumer satisfaction in a cup of Coffee. This study was conducted on a cup of Coffee using quantitative descriptive method. The sample in this study amounted to 100 respondents coffee cup consumers. Data collection technique is by filling out a questionnaire through google form with some questions, then processed using SPSS 26. The results of the T-test showed that there is no partial influence between product quality and consumer satisfaction and there is a partial influence between the quality of service to consumer satisfaction. Simultaneous influence between product quality and service quality on consumer satisfaction. which means that product quality and service quality have a simultaneous influence on consumer satisfaction.